Shriram Transport Finance Company Ltd. : adoption of Fintech - Sahay, Arvind; Tiwari, Tara (London : Indian Institute of Management, Ahmedabad, 2019)
Shriram Transport Finance Company Ltd. (STFCL), the flagship company of the Shriram Group, India's largest player in commercial vehicle finance is trying to transition to a Fintech based model from a Relationship based model in order to provide its end consumers with speed, convenience, choice and savings, as digital transactions had reached an all-time high of 1.11 billion in January 2018 and digital payments were estimated to increase to USD 1 trillion by 2023.
Originally Published InSahay, A., & Tiwari, T. (2019). Shriram Transport Finance Company Ltd.: Adoption of Fintech. IIMA/MAR0508. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Finance companies -- India -- Automation -- Case studies; Finance companies -- India -- Case studies